(untitled) (Journal of the College of Basic Education, 2026)
An individual’s engagement with religious belief represents one of the most profound motivations for faith in the unseen, and it vividly reflects one’s devotion and love for the Creator of the universe. Such engagement plays a pivotal role in cultivating a religious consciousness that upholds society’s commitment to metaphysical and spiritual values. In contrast, materialist inclinations often lure individuals toward hedonism and worldly indulgence, coupled with a tendency to embrace innovation and reinterpretation—especially within religious domains—in ways that align with contemporary cultural norms. This trend has become a key factor in diverting individuals from the path of truth and undermining foundational religious principles. In recent times, this shift has facilitated the infiltration of alien values and concepts into the collective mindset, under the guise of liberation from perceived constraints on instinctual desires. For some, this has escalated into overt or partial forms of atheism. Given the growing prevalence and influence of this phenomenon in the Islamic world, it is imperative to investigate its manifestations and consequences, and to explore effective strategies and practical measures to mitigate its spread. This study aims to examine the most salient negative ramifications of these ideologies, their impact on social life and spiritual environments, and the profound threats they pose to both society at large and the integrity of religious beliefs and legal rulings in particular.